DRUG UTILIZATION STUDY IN OPHTHALMOLOGY OUTPATIENT DEPARTMENT IN A TERTIARY CARE TEACHING HOSPITAL OF WESTERN UTTAR PRADESH, INDIA - JAIN, AMIT KUMAR; Jain, Seema; Sharma, Vikrant; Pandey, Dadan Ji; Shukla, Anand (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: Assessment of drug use pattern especially in developing countries is becoming increasingly necessary to promote the rational use of drugs. The present study was done to investigate the drug utilization pattern in Ophthalmology Outpatient Department (OPD) at Saraswathi Institute of Medical Sciences, Hapur, India, using the World Health Organization (WHO) drug use indicators. Methods: The prescriptions of 1000 outpatients were included and analyzed using a predesigned form to record information from the OPD prescription cards of each patient. Following WHO drug use indicators and additional indices were analyzed: Average number of drugs per prescription, number of encounters with antibiotics, percentage of encounters with injections, percentage of drugs prescribed by their generic names, percentage of drugs prescribed from the National Essential Drug List (NEDL), etc. Results: Prescription analysis showed that the average number of drugs per prescription was 2.92. The drugs were prescribed in the form of eye drops (53.08%), followed by ointments (22.43%), tablets (18.49%), and capsules (5.99%). The dosage form was indicated for all of the drugs prescribed, the frequency of drug administration for 97.5% of the drugs, and the duration of treatment for 82.5% of the drugs prescribed. Antimicrobial agents were the most commonly prescribed drugs followed by lubricants, anti-inflammatory, antiallergic, antiglaucoma drugs, etc. Percentage of drugs prescribed by generic name and from NEDL was 1.19% and 24.45%, respectively. Patient's knowledge of correct dosage was 95%. Conclusion: The prescription writing errors were less, however, there was very low generic prescribing and inadequate information about the duration of therapy in many prescriptions. Keywords: Drug utilization, Ophthalmology, World Health Organization, Generic name.